Prospective Elementary Teachers' Beliefs About Mathematical Myths: A Historical and Qualitative Examination. Issue 1 (2nd January 2020) - Phelps-Gregory, Christine M.; Frank, Martha; Spitzer, Sandy M.
Abstract: Previous research has found that prospective elementary teachers hold beliefs about mathematics that potentially hinder learning, sometimes called "math myths." However, since these research studies were conducted, mathematics education and teacher education in the United States has changed, so more recent work is needed. This historical replication examined current prospective teachers' (PTs') beliefs, using a mixed-methods approach, with the goals of investigating the nature of those beliefs and comparing them to historical trends. Our quantitative and qualitative results help us understand PTs' perceptions of these myths, and our historical comparison reveals many myths appear to be stable and resistant to change. Our work adds nuance to the field's understanding of PTs' beliefs about mathematics and how they have changed (or not) over time. By examining the myths that PTs' perceive as true or false, we can help teacher educators interested in changing these beliefs.